A Corpus-Based Analysis of Future Tense Markers in Indonesian EFL Textbooks for Senior High School - Ikmi Nur Oktavianti; Icuk Prayogi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
A well-designed textbook can enhance the teaching and learning of a foreign language and it should also consider the authenticity aspect of the target language. This paper aims at studying the use of future tense markers (i.e. will, be going to) in three EFL textbooks for senior high school in Indonesia and comparing to one of the biggest English corpora, Corpus of Contemporary American English, to investigate the authenticity of the textbooks. This study employs corpus-based analysis as it focuses on the frequency and collocates of future tense markers. This study, however, delimits the scope in conversations of the textbooks and the spoken sub-corpus. It shows that, although ‘will’ and ‘be going to’ are used in the textbooks and the corpus, there are some distinctions observed, be they the frequency of use or the collocates preceding the future tense markers. As for the semantic of the verb collocates, there seem to have many differences. These differences then need to be revisited and re-evaluated to improve Indonesian EFL textbooks materials to equip the English learners in a foreign language context with actual language use.